Correction of breast deformities after breast-conserving surgery in Chinese women with breast cancer: a narrative review - Wu, Zejun; Zhong, Long; Gu, Jiaxu; Xie, Hongqiang; Guo, Fan (Frontiers in Oncology, 2025)
Breast-conserving therapy (BCT) is a key treatment option for early-stage breast cancer, balancing oncologic control with cosmetic outcomes. However, postoperative breast deformities occur in approximately 25% to 30% of cases, significantly impacting patients’ body image and psychological well-being. Although advances in oncoplastic surgery have demonstrated the safety and efficacy of corrective procedures—effectively improving breast appearance, alleviating anxiety, and enhancing quality of life—the acceptance rate of such surgeries remains relatively low in China. This reluctance is influenced by multiple factors, including personal characteristics, social support, disease-related features, and treatment experiences. This article reviews the necessity and safety of deformity correction after BCT, as well as the factors affecting patients’ willingness to undergo such procedures. The aim is to help clinicians identify suitable candidates for corrective surgery, promote multidisciplinary interventions and decision-making support, and ultimately improve the correction rate and overall quality of life for breast cancer patients.